Analysis of the Concept of Ibn Khaldun's Perspective Learning Method in Islamic Religious Education Learning at Madrasah Ibtidaiyah - Astuti, Binti; Dina, Sarah (Fahmina: Jurnal Pendidikan Islam, 2024)
The concept of the learning method from Ibn Khaldun's perspective is a method used by Islamic religious education teachers in the learning process taking place in class, this method is easy for students to understand in absorbing the subject matter delivered by the teacher. The purpose of this study was to determine the concept of the learning method from the perspective of Ibn Khaldun in learning Islamic religious education. The research method used by the author is a type of qualitative research with descriptive analysis. Data collection is done by interviews and documentation. Furthermore, the data were analyzed descriptively. The findings in this study are that there are several perspective learning methods in learning Islamic religious education that are used by first-grade teachers at Madrasah Ibtidaiyah. There are five methods used by Islamic religious education teachers, namely the method of memorization, exemplary, application, repetition and affection. There are four stages of student development, namely cognitive intelligence, affective intelligence, psychomotor intelligence and social intelligence. To evaluate the learning of Islamic religious education teachers to see the ability of students to absorb lessons, the teacher also provides directions so that students who are slow in understanding can easily follow lessons well.